L’usage territorial du mot terminus dans les écrits de Grégoire de Tours - Pierre-Éric Poble (Bulletin du Centre d’Études Médiévales d’Auxerre)
Gregory of Tours’ lexicon has been studied by several people, but none of them recently paid attention to the word terminus. However, alongside some classic use, this author gives that term an original meaning. This is studied in this article in order to understand why Gregory of Tours uses that word in this way. Is he trying to set out a particular territorialized space located outside the classical boundaries of the city and more or less recently conquered ? This hypothesis opens up new understandings about the territorial organization of local spaces at the beginning of Merovingian times.